Ottelia fengshanensis, a new bisexual species of Ottelia (Hydrocharitaceae) from southwestern China - Li ZZ; Wu S; Zhou CY; Liu Y; Hu GW; Lehtonen S; Wang QF; Chen JM (PENSOFT PUBLISHERS, 2022)
Ottelia fengshanensis, a new species (Hydrocharitaceae) from southwest China is here described and illustrated. Comparing its morphological features to putative close relatives O. guanyangensis, it has 3-4 flowers (vs. 2-5) each spathe, hexagonal-cylindric fruit, white styles (vs. yellow), green leaves (vs. dark green) and fruit tiny winged (vs. winged obviously). Molecular phylogenetic investigation of four DNA sequences (ITS, rbcL, trnK5' intron and irnS-irnG) and the Poisson Tree Processes model for species delimitation (PTP) analysis, further resolves O. fengshanensis as a new species that is close to O. guanyangensis with distinct support.